Comparison of community‐onset healthcare‐associated and hospital‐acquired urinary infections caused by extended‐spectrum beta‐lactamase‐producing Escherichia coli and antimicrobial activities. Issue 7 (16th February 2015) - Saltoglu, N.; Karali, R.; Yemisen, M.; Ozaras, R.; Balkan, I. I.; Mete, B.; Tabak, F.; Mert, A.; Hondur, N.; Ozturk, R.
Summary Objective We aimed to compare community‐onset healthcare‐associated (CO‐HCA) and hospital‐acquired (HA) urinary tract infections (UTIs) caused by extended‐spectrum beta‐lactamase (ESBL)‐producing Escherichia coli in terms of epidemiology, clinical outcomes and antimicrobial activities. Methods Patients from both groups with ESBL‐producing E. coli detected by urine culture between January 2009 and January 2011 were included in this retrospective study. Relevant demographical, microbiologic and clinical data were obtained from case records. Results A total of 173 patients (mean age of 58 years, 74% female) were included, of whom 75 (43.4%) had a CO‐HCA UTI and 98 (56.6%) had an HA UTI. Eighty (46.2%) patients had more than one comorbid disease, of whom 57 (32.5%) had urological problems. The most common clinical manifestations were pyelonephritis (43.9%) and urosepsis (16.2%). An age of > 65 years (p = 0.005) in addition to urinary catheterisation (p = 0.001), urosepsis (p = 0.001) and mortality (p = 0.001) were significantly more common in the HA UTI group. Acute cystitis (p = 0.027), complicated cystitis (p = 0.001) and non‐urologic neoplasm (p = 0.032) were significantly more common in the CO‐HCA UTI group. No isolate was resistant to carbapenems or fosfomycin. Sensitivities to nitrofurantoin, amikacin, trimethoprim sulfamethoxazole‐trimoxazole and quinolones were 97.6%, 89%, 29.4% and 17.9% respectively. Both groups showed similar rates of antibiotic resistance. Conclusion ESBL‐producing E. coli should be taken into consideration in patients with a CO HCA UTI, not only in hospital settings but also in outpatient settings. We suggest ertapenem as a first‐line empirical treatment for patients with an upper UTI and fosfomycin and nitrofurantoin for those with a lower UTI when ESBL‐producing E. coli is suspected.